Preparation and application of near-infrared laser photothermal conversion and wave-absorbing composite material

By synthesizing cobalt iron bialloy nanoparticles on cotton-derived carbon materials, a near-infrared laser photothermal conversion and wave absorption composite material was prepared, which solved the existing problems of anti-garment rigidity and single performance, and achieved efficient photothermal conversion and wave absorption performance, which was suitable for complex military applications.

CN119711179AInactive Publication Date: 2025-03-28HEBEI UNIV OF SCI & TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411877931.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The rigid sensing plates used in existing countermeasures increase the burden on soldiers, and a single-performance material is difficult to meet the complex military application environment, especially in terms of near-infrared laser absorption and induction.

Method used

Through hydrothermal synthesis and high-temperature pyrolysis calcination, cobalt iron bialloy nanoparticles are firmly anchored on the surface of cotton-derived carbon materials, and a near-infrared laser photothermal conversion and wave absorption composite material was prepared. The material is based on a cotton-derived carbon film, supported by CoFe layered double hydroxide and Co metal organic frame, and coated with polydimethylsiloxane (PDMS) to form a flexible composite material.

Benefits of technology

It realizes the efficient photo-thermal conversion and excellent wave absorption performance of near-infrared lasers. The material has the advantages of lightweight, multifunctional, and flexibility, and is suitable for military laser shooting and sensing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119711179A_ABST
    Figure CN119711179A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a near-infrared laser photothermal conversion and wave-absorbing composite material, and belongs to the technical field of composite materials. According to the preparation method, CoFe layered double hydroxide (CoFe-LDH) and Co metal organic framework (Co MOF) are sequentially grown on cotton fibers in situ through a simple hydrothermal synthesis method, then cotton fabrics loaded with metal ions are annealed and carbonized at different temperatures through a calcination pyrolysis method, and composite films of different specifications are prepared. And finally, polydimethylsiloxane (PDMS) is used for solid sealing, so that the mechanical property and the durability are improved. And a good foundation is provided for discovery of novel multifunctional materials and development of an induction technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and in particular relates to the preparation and application of a near-infrared laser photothermal conversion and wave-absorbing composite material. Background Art

[0002] With the accelerated development of modern military and communication technologies, researchers have begun to pay extensive attention to the production of multifunctional materials that can absorb electromagnetic waves and convert energy to improve military combat capabilities. Near-infrared (NIR) lasers can concentrate high energy in a small range, while NIR light, which is invisible to the human eye, also meets the advantage of hiding in night operations. Therefore, near-infrared lasers can be used as military shooting weapons. At present, a confrontation suit that can be worn on the shooter is used in systems such as real-life combat, laser simulation shooting training, and laser confrontation shooting. It is used to receive laser irradiation and collect the state and position of the light spot hit by computer processing data to display the effect of being hit. The rigid induction plate used in existing confrontation clothing is undoubtedly a "burden" for soldiers' combat operations. In addition, the military field often requires a complex application environment, which makes it difficult for materials with a single performance to meet practical applications. Many existing magnetic metal absorbing materials still have problems such as narrow absorption bandwidth and single coverage frequency band. Therefore, the development of a lightweight, multifunctional, flexible composite material with effective absorption and NIR sensing properties provides a new attempt to protect soldiers and maintain stable operation of military operations. Summary of the invention

[0003] In view of the above technical problems, the present invention proposes the preparation and application of a near-infrared laser photothermal conversion and wave absorbing composite material. Cobalt-iron dual alloy nanoparticles are firmly anchored on the surface of cotton-derived carbon materials through hydrothermal synthesis and high-temperature pyrolysis calcination to obtain a composite material with photothermal conversion and excellent wave absorbing properties, which provides a good foundation for the discovery of new multifunctional materials and the development of sensing technology.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] Technical purpose 1: A near-infrared laser photothermal conversion and wave absorbing composite material, which has a cotton-derived carbon film as a substrate, and CoFe layered double hydroxide (CoFe-LDH) and Co metal organic framework (CoMOF) are loaded on the cotton fiber in sequence.

[0006] Technical purpose 2: A method for preparing a near-infrared laser photothermal conversion and wave absorbing composite material, comprising the following steps:

[0007] (1) Dissolve cobalt nitrate and ferric nitrate in pure water, add urea and ammonium fluoride, and stir magnetically for 15 minutes to obtain a precursor solution that changes from orange-red to pink;

[0008] (2) immersing the cotton fabric (CF) washed with ethanol in the precursor solution and transferring it to a hydrothermal reactor for hydrothermal reaction to in situ grow CoFe-LDH on the surface of the cotton fiber;

[0009] (3) Dissolving cobalt nitrate and 2-methylimidazole in water respectively and mixing them to obtain a mixed solution, immersing the sample after the hydrothermal reaction in the mixed solution and aging it for 1 hour, so as to continue to grow CoMOF in the gaps on the surface of the cotton fiber where CoFe-LDH is grown, and obtaining CoFe-LDH@Co MOF cotton fabric (CoFe-LDH@Co MOF@CF, abbreviated as CoFe@CF) after washing and drying;

[0010] (4) The CoFe-LDH@Co MOF cotton fabric is subjected to pyrolysis and carbonization treatment to obtain a near-infrared laser photothermal conversion and wave absorbing composite material (CoFe@CCF-T, abbreviated as CCF-T).

[0011] Furthermore, in the precursor solution, the molar ratio of cobalt in cobalt nitrate to iron in ferric nitrate is 1:1; and the molar ratio of urea to ammonium fluoride is 1:1.

[0012] Furthermore, the conditions of the hydrothermal reaction are: heating at 120° C. for 12-18 hours.

[0013] Furthermore, in the mixed solution, the molar ratio of 2-methylimidazole to cobalt nitrate is (12.5-13):1.

[0014] Furthermore, the specific process of the pyrolysis carbonization treatment is: under the protection of inert argon in a vacuum tube furnace, heating to 700-1000°C (such as 700°C, 800°C, 900°C, 1000°C) at a rate of 5°C / min, and continuously calcining at the corresponding temperature for 1-1.5h.

[0015] Technical purpose three: Application of a near-infrared laser photothermal conversion and wave-absorbing composite material in the field of military laser shooting and sensing.

[0016] Technical purpose four: A near-infrared laser photothermal conversion and wave absorbing flexible composite material, which uses polydimethylsiloxane (PDMS) to encapsulate the near-infrared laser photothermal conversion and wave absorbing flexible composite material with carbon thin film to obtain a near-infrared laser photothermal conversion and wave absorbing flexible composite material (CoFe@PCCF-T, abbreviated as PCCF-T).

[0017] The reaction principle of the present invention: CoFe@PCCF-T composite material is constructed by hydrothermal synthesis, high temperature pyrolysis calcination and PDMS coating, such as Figure 1As shown. The abundant OH-functional groups in cotton fabrics can promote the binding with metal ions through electrostatic interaction and coordination. Simple hydrothermal processes can induce decarboxylation, condensation and dehydration reactions to promote the formation of nanoscale pores. At the same time, it mainly involves the gradual hydrolysis of NH4F and the decomposition of CO(NH2)2 to produce OH-ions to obtain an alkaline solution, which reacts with Co from Co(NO3)2·6H2O and Fe(NO3)3·9H2O. 2+ and Fe 3+ Ion binding induces uniform nucleation and crystal growth of CoFe hydroxide on the fiber (Formula (1)-(3)). In addition, the formation of CoFe-LDH with a large aspect ratio and abundant metal active sites provides growth sites for Co MOF, allowing it to grow along the direction of the nanoneedles. Then, the precursor fabric is converted into reduced carbon material by high-temperature pyrolysis annealing, and the metal ions are converted into corresponding metal alloy particles tightly attached to the surface of each carbon fiber.

[0018]

[0019] Co 2+ +Fe 3+ +OH - →CoFe-LDH (3)

[0020] The near-infrared laser photothermal conversion and wave absorbing flexible composite material based on the cotton-derived carbon film of the present invention has the following advantages:

[0021] (1) Biomass-derived carbon materials are sustainable, low-cost, high in carbon content and highly compatible. Their surface chemical properties are conducive to interfacial chemical reactions and are highly consistent with the general direction of green functional materials. The entangled 3D structure of cotton fiber-derived carbon materials helps to build a stable conductive network, and cotton fabrics can still inherit the original complete microstructure after high-temperature pyrolysis;

[0022] (2) Compared with magnetic oxides, magnetic alloy absorbers (cobalt-iron bimetallic nanoparticles) have more variable and tunable electromagnetic properties;

[0023] (3) After near-infrared laser irradiation, the laser energy reaching the film is rapidly converted into ambient heat through electron-phonon and phonon-phonon processes, which can achieve an effective photothermal conversion effect;

[0024] (4) With cotton-derived carbon film as a flexible substrate, the localized surface plasmon resonance (LSPR) and dielectric electromagnetic conductance of magnetic metal ions and carbon fibers jointly construct a photothermal signal conversion and microwave absorption network of the composite material. The properties of the composite material can be adjusted and changed by changing the carbonization temperature and other conditions, which is attributed to the loading amount and surface / interface chemical reaction of the resulting carbon composite material;

[0025] (5) PDMS curing and encapsulation can effectively prevent the metal particles on the surface of carbon fiber from falling off and water and oxygen from entering the interior, thereby improving the mechanical properties of the material and further ensuring its long-term stability. At the same time, the thickness of the composite film is only about 1.67 mm, showing high light transmittance and ultra-thinness, combining load-carrying characteristics with scalability under harsh environmental conditions such as rain and snow, while avoiding the shortcomings of poor environmental resistance of the coating on the surface and high maintenance costs. Using derived carbon as a flexible matrix is ​​of great significance for the development of structurally functionalized flexible polymer-based composite materials that are lightweight, portable, and have excellent photothermal and wave-absorbing properties.

[0026] Compared with the prior art, the present invention has the following advantages and technical effects:

[0027] (1) It is of great significance to combine sensitive materials with flexible substrates to design lightweight, portable, high-performance structural multifunctional green materials. (2) The preparation process of the composite material is green and environmentally friendly, the reagents used are non-toxic and harmless, and no harmful substances are produced. It has the advantages of sustainability and low cost, and is highly in line with the general development trend of green production. (3) This composite film has excellent photothermal conversion and microwave absorption properties, which can meet the short-term rapid response under low-power light radiation and the effective absorption capacity covering the C-Ku band. Its reusability and high stability provide new potential for the development and research of flexible multifunctional composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0029] Figure 1 The experimental flow chart of the present invention for preparing near-infrared laser photothermal conversion and wave-absorbing flexible composite materials;

[0030] Figure 2 SEM images of CoFe@PCCF-T in different states, including (ab) CoFe-LDH@CF, (ce) CoFe-LDH@Co MOF@CF, (f) CoFe@CCF-1000, (g) CoFe@PCCF-1000 sealed with PDMS; EDS element mapping, including (h) five elements of C, O, Co, Fe, and Si; digital image photos, including (i) CoFe-LDH@Co MOF@CF and CoFe@PCCF-1000, (j) CoFe@PCCF-1000 under indoor lighting; (k) digital image of water contact angle of CoFe@PCCF-1000;

[0031] Figure 3(a) XPS spectra of CoFe@CF and CCF-1000, (b) high-resolution XPS of C 1s, (c) N1s, (d) Co 2p and (e) Fe2p, (f) XRD pattern of CoFe@CCF-T (abbreviated as CCF-700, CCF-800, CCF-900 and CCF-1000);

[0032] Figure 4 Temperature curves of CF and CoFe@PCCF-T (abbreviated as PCCF-T) at different laser irradiation distances, (a) 100 cm, (b) 200 cm; temperature curves of PCCF-1000 at different irradiation distances during the cyclic switching process, (c) 100 cm, (d) 200 cm;

[0033] Figure 5 Schematic diagram of thermal imaging test system of PCCF-T under laser irradiation;

[0034] Figure 6 The digital images of PCCF-1000 taken at different distances by a near-infrared over-the-horizon observer during the photothermal test, where (a) the laser irradiation distance is 100 cm and (b) the laser irradiation distance is 200 cm; the digital images taken at different distances by a thermal imager, where (c) the laser irradiation distance is 100 cm and (d) the laser irradiation distance is 200 cm;

[0035] Figure 7 are the electromagnetic parameters of CoFe@PCCF-T, where (a) the real part of the dielectric constant ε′, (b) the imaginary part of the dielectric constant ε″, and (c) the dielectric loss tangent tanδ ε , (d) real part of magnetic permeability μ′, (e) imaginary part of magnetic permeability μ″, (f) magnetic loss tangent tanδ μ ;

[0036] Figure 8 The reflection loss 2D and 3D graphs and the frequency dependence graph of the reflection loss RL curve of CoFe@PCCF-T, where (ac) PCCF-700, (df) PCCF-800, (gi) PCCF-900, (jl) PCCF-1000;

[0037] Fig. 9 RL peak and impedance matching of CoFe@PCCF-T |Z in / Z0|Figure, (a) PCCF-700, (b) PCCF-800, (c) PCCF-900, (d) PCCF-1000;

[0038] Fig.10Diagram of the photothermal conversion and electromagnetic wave absorption mechanism of CoFe@PCCF-T. DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0044] The "room temperature" mentioned in the present invention refers to 25±2°C unless otherwise specified.

[0045] The raw materials used in the present invention are all purchased from the market.

[0046] The technical solution of the present invention is further illustrated by the following embodiments.

[0047] The experimental raw materials used in the following examples of the present invention are shown in Table 1, and the experiments and equipment used are shown in Table 2.

[0048] Table 1 Experimental raw materials

[0049]

[0050] Table 2 Experimental and test equipment

[0051]

[0052]

[0053] Among them, ferric nitrate (Fe(NO3)3·9H2O, >99%), cobalt nitrate (Co(NO3)2·6H2O, >99%), urea (CO(NH2)2, >99%), ammonium fluoride (NH4F, ≥98%), and 2-methylimidazole (2-MIM, >98%), all chemical reagents were of analytical grade.

[0054] Figure 1 The figure is a flow chart of the experiment of the present invention.

[0055] Example 1

[0056] A method for preparing a near-infrared laser photothermal conversion and wave absorbing flexible composite material comprises the following steps:

[0057] (1) Cobalt nitrate and ferric nitrate were dissolved in 30 mL of pure water (the molar ratio of Fe to Co was 1:1), and then 0.51 g of urea and 0.3 g of ammonium fluoride were sequentially mixed with the above solutions and magnetically stirred for 15 min to obtain a precursor solution that rapidly changed from orange-red to pink;

[0058] (2) the cotton fabric (CF) washed with ethanol was immersed in the precursor solution and transferred to a hydrothermal reactor and heated at 120 °C for 18 h to in situ grow CoFe-LDH on the cotton fiber surface;

[0059] (3) 0.46 g of cobalt nitrate was dissolved in 50 mL of water as solution A, and 1.314 g of 2-methylimidazole was dissolved in another 50 mL of water as solution B. Solution B was slowly poured into solution A and mixed evenly. The fabric obtained in step (2) was immersed in the mixed solution and aged for 1 h, so as to continue to grow 2D sheet-like Co MOF in the gaps on the surface of the cotton fiber where CoFe-LDH was grown. After washing and drying, CoFe-LDH@Co MOF@CF (abbreviated as CoFe@CF) was obtained.

[0060] (4) The obtained fabric was heated to different temperatures (700°C, 800°C, 900°C, 1000°C) at a rate of 5°C / min in a vacuum tube furnace under the protection of inert argon gas, and continuously calcined at the corresponding temperature for 1 h to obtain near-infrared laser photothermal conversion and wave absorbing composite material CoFe@CCF-T (abbreviated as CCF-T, where T is temperature, i.e. CCF-700, CCF-800, CCF-900, CCF-1000);

[0061] (5) PDMS main agent and epoxy silane coupling curing agent are mixed in a mass ratio of 10:1, and the mixture is diluted with twice the mass of n-hexane and stirred until completely dissolved. The obtained colloidal solution is applied to the surface of the obtained carbon film to form a uniform liquid layer, and gradually cured to 80°C for 4 hours to obtain near-infrared laser photothermal conversion and wave absorbing flexible composite material CoFe@PCCF-T (abbreviated as PCCF-T, where T is temperature, i.e. PCCF-700, PCCF-800, PCCF-900, PCCF-1000).

[0062] Performance Testing

[0063] 1. Structural and morphological characteristics

[0064] Scanning electron microscopy (SEM) was used to observe the surface morphology of the composite films under different states, energy dispersive spectroscopy (EDS) was used to visually observe the elemental composition of the materials, and a contact angle tester (JC2000D1) was used to measure the hydrophobicity of the materials.

[0065] Figure 2 SEM images of CoFe@PCCF-T in different states, including (ab) CoFe-LDH@CF, (ce) CoFe-LDH@Co MOF@CF, (f) CoFe@CCF-1000, (g) CoFe@PCCF-1000 encapsulated by PDMS; EDS element mapping, including (h) five elements: C, O, Co, Fe, and Si; digital image photos, including (i) CoFe-LDH@Co MOF@CF and CoFe@PCCF-1000, (j) CoFe@PCCF-1000 under indoor lighting; (k) digital image of the water contact angle of CoFe@PCCF-1000.

[0066] exist Figure 2 As can be seen in (ab), CoFe-LDH grows anisotropically on cotton fibers in situ, forming a layer of high-density and rich and uniform nano-spike LDH after solvent thermal synthesis. Figure 2 As can be seen in (ce), the cotton fabric with CoFe-LDH grown on it was further immersed in a Co 2+ In the 2-methylimidazole ligand MOF aqueous solution, the two-dimensional nanosheets of Co MOF were arranged at the growth site. It can be seen that the CF chain is completely wrapped by the growing CoFe-LDH and Co MOF, forming an interconnected sea urchin flower needle structure on the entire surface without obvious shedding. Figure 2(f) shows CoFe@CCF-1000 after pyrolysis carbonization annealing at 1000°C. The CoFe nanoneedles and imidazole ligands of MOF grown in situ on CF can be converted into reduced carbon after annealing, which inhibits the sharp shrinkage of the fiber during high-temperature carbonization, further acts as a reducing agent for metal ions and a dispersant for metal particles, and forms magnetic CoFe three-dimensional alloy particles and a carbon network conductive layer. Finally, it can be seen from Figure (g) that PDMS tightly wraps the entangled carbon fibers and the loaded alloy nanoparticles, and the surface also changes from rough to smooth, forming a translucent film.

[0067] The chemical structure and element distribution of alloy particles and carbon fibers were further demonstrated by EDS element mapping analysis. Figure 2 In (h), it can be seen that the main elements are Fe, Co, C, O, and Si, and are evenly distributed in different colors. The Fe / Co element content ratio is close to 1:1, which is almost the same as the added content. In addition, Figure 2 (i) shows the actual images of CoFe-LDH@CoMOF@CF and CoFe@PCCF-1000. After carbonization at 1000°C, the cotton fabric shrinks in volume and its color changes from bright purple to black-gray, but it still maintains its basic appearance and complete carbon network structure. Figure 2 The middle (j) shows its high transparency and ultra-thinness. Figure 2 As can be seen in (k), the water contact angle (CA) of the carbon fabric encapsulated by PDMS is 108.45°, indicating that it has strong hydrophobicity, can isolate water and oxygen, and greatly extend its service life.

[0068] 2. XPS and XRD analysis

[0069] XPS was used to identify the elemental state and chemical composition of the composites, as well as the transformation of the elemental state by high temperature calcination. Figure 3 (a) XPS spectra of CoFe-LDH@Co MOF@CF (abbreviated as CoFe@CF) and CoFe@CCF-1000 (abbreviated as CCF-1000), (b) high-resolution XPS of C1s, (c) N1s, (d) Co 2p and (e) Fe 2p, (f) XRD pattern of CoFe@CCF-T (abbreviated as CCF-700, CCF-800, CCF-900 and CCF-1000, respectively).

[0070] like Figure 3 As shown, it can be seen that they are mainly composed of six elements: Co, Fe, O, N, C, and Si. Figure 3As shown in (be), the high-resolution XPS fine spectra of C, N, Co, and Fe elements were obtained and fitted. Compared with CoFe@CF, the C=O peak (288.8eV) and CN (286.4eV) peaks of CCF-1000 were weakened, while the C=C / CC peak at 284.8eV was enhanced. In addition, the pyrrolic-N peak (400.7eV) derived from MOF was weakened or even disappeared, the pyridine-N peak (398.7eV) was also significantly reduced, and a very small pyridine-N-oxide peak (403.6eV) appeared. This phenomenon is mainly due to the carbonization of the cellulose molecular chain and the gradual removal of oxygen-containing functional groups, as well as the decomposition of the 2-methylimidazole ligand of MOF at high temperature. It is well known that oxygen-containing anions in complex metal compounds can cause changes in charge states, thereby affecting electronic parameters. In the high-resolution Co 2pXPS spectrum, the peaks of CoFe@CF at 781.2 eV and 797.7 eV correspond to Co 3+ Co 2p 3 / 2 and Co 2p 1 / 2 , and 783.6 eV corresponds to Co 2+ Co 2p 3 / 2 The next peak is accompanied by a satellite band at 803.4 eV, indicating the presence of high-spin Co in the LDH material. ll The new peaks of CCF-1000 at 779.6eV and 794.7eV can be identified as cobalt, indicating that Co atoms are carburized and reduced to the metallic state during annealing. Similarly, for the Fe 2p XPS peak, a new satellite peak appears at 720.1eV in CCF-1000 after calcination and annealing, corresponding to metallic Fe.

[0071] During the pyrolysis process, the -OH groups in the fabric initially increase due to the rupture of the glucose units, and then decrease due to dehydration at higher temperatures to form =CH or C=O. During this period, the -OH, CC and C=O bonds break due to dehydration, dehydrogenation or cracking reactions. Therefore, C=C bonds are formed when the carbonization temperature is high. In addition, oxygen-containing functional groups such as COC remain relatively stable during the pyrolysis process. XRD technology was used to analyze the structure of CCF-T after pyrolysis and carbonization, such as Figure 3 As shown in (f). The CCF sample shows a broad characteristic diffraction peak at 26.5°, corresponding to the (002) plane of amorphous carbon. This phenomenon indicates that the structure of cotton fabric has been transformed into carbon material, which is consistent with the biomass-derived carbon materials reported in the past. In addition, the three diffraction peaks of CCF-700 at 35.4°, 56.9°, and 62.5° are consistent with those of cobalt iron oxide (Co 0.62 Fe 1.38)FeO4 (ICSDNo.88-2152) (311), (511), (440) planes. The three obvious diffraction peaks of CCF-800, CCF-900 and CCF-1000 at 44.8°, 65.3° and 82.7° are highly consistent with the (110), (200), (211) planes of body-centered cubic structure CoFe alloy (JCPDS No.49-1568). However, CCF-800 has more heterogeneous peaks compared with CCF-900 and CCF-1000. Like CCF-700, there are relatively more heterogeneous peaks, including iron oxide (Fe2O3), cobalt oxide (CoO) and cobalt iron hydroxide. This phenomenon can explain that CoFe alloy particles loaded on the fiber can be generated at least at a calcination temperature of 800℃, but not completely. The height of the unique diffraction peak decreases with increasing temperature, indicating that the metallic CoFe state is more stable. Therefore, the pyrolysis temperature has a significant effect on the state of the loaded metal, and the mixed metal oxides of Co and Fe gradually transform into CoFe stereo alloys as the increase in carbonization temperature leads to changes in the size of metal crystallites.

[0072] 3. Near-infrared laser photothermal conversion test

[0073] The intrinsic light absorption of biomass-derived carbon materials and the localized surface plasmon resonance (LSPR) effect of metal nanoparticles are important means of NIR photothermal conversion. In order to study the photothermal conversion characteristics of CoFe alloy particle cotton-derived carbon films at different carbonization temperatures, the surface temperature change of CoFe@PCCF-T was tested using 980nm near-infrared laser irradiation technology at an indoor temperature of about 16℃. The wavelength and power intensity of the laser determine the degree of damage to certain human tissues. Considering the issue of human safety, a low-power near-infrared laser irradiation of 200mW, a wavelength of 980nm and a fixed current of 0.25A was used. Figure 4 Temperature curves of CF and CoFe@PCCF-T (abbreviated as PCCF-T, i.e. PCCF-700, PCCF-800, PCCF-900 and PCCF-1000) at different laser irradiation distances, where (a) is 100 cm and (b) is 200 cm; temperature curves of PCCF-1000 at different irradiation distances during the cyclic switching process, where (c) is 100 cm and (d) is 200 cm.

[0074] Figure 4 The figure shows the change of the film surface temperature over time under laser irradiation. In addition, considering the practical application of laser shooting, the effect of irradiation distance on temperature was further tested and studied, with the distance ranging from 100cm to 200cm. Figure 4In (a), pure CF has no photothermal conversion capability and remains at around ambient temperature. However, after 30 seconds of laser irradiation, the local surface temperature of the alloy carbide film can basically reach an equilibrium state, indicating that the laser energy of the film is rapidly converted into ambient heat through electron-phonon and phonon-phonon processes. The local surface steady-state temperature of PCCF-1000 can reach 118.0°C and can reach 74.5°C in just 3 seconds. Furthermore, at a distance of two meters Figure 4 In (b), PCCF-1000, which performs well, can also reach a steady-state temperature of 48.6°C within 30s. In contrast, the photothermal capacity of PCCF-700 is not as good as other films, which may be due to the low carbonization pyrolysis temperature and the incomplete formation and attachment of CoFe alloy nanoparticles to the fibers.

[0075] Subsequently, a cyclic switching experiment was performed to evaluate the durability of PCCF-T in photothermal conversion applications. Under constant power, the PCCF-1000 suspended sample was placed at a distance of 100 cm and 200 cm, the laser irradiation was turned on for 30 seconds to reach the steady-state temperature, and then turned off to allow the sample to cool to room temperature. This process was repeated four times. Figure 4 As shown in (cd), the temperature of the film after irradiation for 30s is 118℃ and 48.6℃ respectively, and drops to 16.7℃ within 10s after being turned off. When laser irradiation is resumed, the temperature can rise to the respective steady-state temperature again. The results show that this film has good photothermal stability and reusability, and meets the short-term fast response under low-power light radiation.

[0076] PCCF-T exhibits high photothermal conversion efficiency and photothermal responsiveness, and has great potential as a thermal imaging device. The inventors established a self-developed device system to demonstrate their near-infrared thermal imaging performance. Figure 5 Schematic diagram of the thermal imaging test system of CoFe@PCCF-T (abbreviated as PCCF-T) under laser irradiation.

[0077] like Figure 5 As shown. The PCCF-T sample is placed on a flat plate for laser irradiation treatment, and the surface temperature of the sample is monitored in real time through an infrared thermal imager and a computer system. Since near-infrared light is not within the visible line of sight of humans, the human eye alone cannot observe the light, so it is necessary to use a near-infrared light over-the-horizon observer to check the light spot status, such as Figure 6 shown.

[0078] Figure 6The digital images of CoFe@PCCF-1000 (abbreviated as PCCF-1000) taken at different distances by a near-infrared over-the-horizon observation instrument during the photothermal test, where (a) the laser irradiation distance is 100 cm, and (b) the laser irradiation distance is 200 cm; the digital images taken at different distances by a thermal imager, where (c) is the laser irradiation distance of 100 cm, and (d) is the laser irradiation distance of 200 cm. Figure 6 As can be seen from (ab) in , as the distance increases from 100 cm to 200 cm, the observed spot area also increases, they change from approximately circular to elliptical, and the illuminated area also becomes larger. Figure 6 It can be seen in (cd) that in the thermal imaging photos of PCCF-1000 at different laser irradiation distances, the luminous area gradually increases and the local temperature of the surface gradually increases.

[0079] 4. Electromagnetic wave absorption performance test

[0080] In order to analyze the electromagnetic wave absorption characteristics of the composite material, CoFe@PCCF was cut into coaxial rings with an inner diameter of 3.04 mm and an outer diameter of 7 mm. The electromagnetic parameters in the frequency range of 2-18 GHz were measured using a vector network analyzer, such as Figure 7 shown.

[0081] Figure 7 are the electromagnetic parameters of CoFe@PCCF-T (abbreviated as PCCF-T, i.e. PCCF-700, PCCF-800, PCCF-900 and PCCF-1000) composite materials, where (a) the real part of the dielectric constant ε′, (b) the imaginary part of the dielectric constant ε″, (c) the dielectric loss tangent tanδ ε , (d) real part of magnetic permeability μ′, (e) imaginary part of magnetic permeability μ″, (f) magnetic loss tangent tanδ μ Complex dielectric constant (ε r =ε'-ε") and magnetic permeability (μ r =μ'-μ') are two main factors affecting the absorption capacity, where the real part (ε' and μ') represents the ability to store electromagnetic energy, and the imaginary part (ε' and μ') represents the dissipation capacity. In addition, the dielectric loss tangent (tanδ ε =ε” / ε') and magnetic loss tangent (tanδ μ =μ” / μ') evaluates the dielectric and magnetic loss characteristics of the material.

[0082] exist Figure 7In (a and b), the charge polarization, dipole polarization and interface polarization generated by the loading of CoFe particles on carbon fibers cause larger ε' and ε". Under the condition of applied electric field, a large number of point defects on the surface of the material redirect the dipoles, enhancing the interface polarization to dissipate microwave energy. According to the free electron theory, ε" = 1 / 2πρfε0, the larger the ε", the higher the conductivity. Secondly, the complex dielectric constant of the material has significant fluctuations and obvious frequency dependence, which indicates that CoFe@PCCF composites can provide more energy storage and polarization capabilities. Figure 7 In (cf), μ' and μ" are close to 1 and 0 respectively, and tanδ ε Higher than tanδ μ Obviously, dielectric loss is the main form of electromagnetic wave attenuation for this material. Although magnetic loss is not dominant in electromagnetic wave attenuation, there are still potential loss mechanisms. In the GHz band, magnetic loss mainly includes hysteresis loss, natural resonance, exchange resonance and eddy current loss. Because the electromagnetic wave field is relatively weak, there is no hysteresis loss. Eddy current loss can be expressed as C0 (C0 = μ) (μ') -2 f -1 ), when C0 is constant with frequency, the magnetic loss is mainly determined by eddy current loss. However, the μ' and μ" of the materials fluctuate greatly in the range of 2-18 GHz, indicating that eddy current loss has little contribution to the magnetic loss. Therefore, natural resonance and exchange resonance play an important role in magnetic loss. With the increase of temperature, the composite permeability increases, especially PCCF-900 performs better.

[0083] According to electromagnetic transmission line theory, the smaller the reflection loss RL (dB), the better the material's wave absorption performance. An RL value below -10dB means that more than 90% of electromagnetic waves are absorbed, and the corresponding frequency range is called the effective absorption bandwidth (EAB). Figure 8 2D and 3D graphs of reflection loss and frequency dependence graph of reflection loss RL curve of CoFe@PCCF-T (abbreviated as PCCF-T, i.e. PCCF-700, PCCF-800, PCCF-900 and PCCF-1000), where (ac) PCCF-700, (df) PCCF-800, (gi) PCCF-900, (jl) PCCF-1000.

[0084] from Figure 8 As can be seen from (gi), PCCF-900 exhibits the best performance, with RL min The RL of PCCF-1000 is -23.03dB and the EAB is 4.53GHz. minAchieved -20.16dB, EAB at 3.42GHz (jl). Secondly, PCCF-800 has RL at 2.6mm min The EAB is 4.14 GHZ (df) and the EAB is -17.63 dB. When the electromagnetic wave enters the interior of the material, it is repeatedly scattered by the cubic particles, which increases the propagation path. The MOF-derived carbon matrix, as a conductive carbon network, inherits the large surface area and porosity of the MOF precursor, and the electromagnetic wave is greatly attenuated. However, the effect of PCCF-700 is not as good as that of other samples. At 1.8 mm RL min Only −10.69 dB(ac) was achieved, which may be attributed to the fact that the magnetic particles did not form a cubic morphology due to the relatively low carbonization temperature and the imidazole ligands of the MOF were not completely converted into the reduced carbon matrix.

[0085] To further illustrate the potential mechanism of enhanced microwave absorption in PCCF-T, the impedance matching values ​​of the materials were calculated to analyze their incident microwave capture and attenuation capabilities, which can be expressed as Z = |Zin / Z0| = (μ r / ε r ) 1 / 2 Good impedance matching requires Z to be equal to or infinitely close to 1.0, which is conducive to the incident electromagnetic wave being absorbed into the interior of the material rather than being reflected back to the absorbing surface. Fig. 9 RL peak and impedance matching of CoFe@PCCF-T (abbreviated as PCCF-T, namely PCCF-700, PCCF-800, PCCF-900 and PCCF-1000) |Z in / Z0|Figure, (a) PCCF-700, (b) PCCF-800, (c) PCCF-900, (d) PCCF-1000.

[0086] from Fig. 9 It can be seen that, as in the above analysis, PCCF-900 shows the best impedance matching at 1.6 mm, which is closest to 1.0, corresponding to RL min Curve. The overall trend of PCCF-700 is low, but the Z values ​​of PCCF-800 and PCCF-1000 are both higher than 1.0. In addition, 2-18GHz can be further divided into S band (2-4GHz), C band (4-8GHz), X band (8-12GHz), and Ku band (12-18GHz). The reflection loss of CoFe@PCCF-900 composite material can cover the C-Ku band, and materials of different thicknesses cover different frequency bands. Therefore, CoFe@PCCF can show good light weight, wide absorption band and thin matching thickness.

[0087] 5. Photothermal conversion and electromagnetic wave absorption mechanism of CoFe@PCCF

[0088] Based on the above characterization and performance results, Fig.10 The photothermal and electromagnetic wave absorption mechanism of CoFe@PCCF-T was proposed in this paper. After heat treatment, a large amount of impurities were removed from the sample, and CoFe particles were synthesized by in-situ annealing to form a three-dimensional connected electromagnetically conductive carbon network. The multi-component carbon fibers and CoFe particles provide a rich multi-interface, which promotes interfacial polarization and effective anisotropic energy. Other defects lead to dipole polarization, realizing the absorption of microwave energy and the conversion of light energy to thermal energy. The magnetic Co particles derived from MOF may also produce weak magnetic losses. Their special uneven surface structure can provide additional more effective scattering and reflection area for electromagnetic waves, thereby increasing the ability of electromagnetic wave dissipation and impedance matching. This shows that CoFe@PCCF-T composites may become promising candidates for excellent photothermal conversion and microwave absorption materials.

[0089] In summary, the present invention uses a simple hydrothermal synthesis method and a high-temperature pyrolysis carbonization method, with cotton-derived carbon film as the substrate, and utilizes the electrostatic interaction between positive and negative charges to in-situ grow double metal hydroxides, and then prepares CoFe@PCCF flexible composite materials of different specifications through annealing and carbonization. By changing the carbonization temperature and adjusting other conditions, the influence of the material on the near-infrared laser photothermal conversion ability and the wave absorption performance was explored, and its hydrophobicity, reusability, stability, etc. were tested. The results show that when the carbonization temperature is 900°C, the electromagnetic wave attenuation performance of CoFe@PCCF-900 is the best, and the RL of the material is min The EAB can reach 4.53 GHz when the thickness is only 1.6 mm. In addition, by changing the thickness of the material, its EAB can cover the C-Ku band. In addition, when the carbonization temperature is 1000 °C, the best photothermal conversion performance of CoFe@PCCF-1000 is obtained. The local surface temperature can be rapidly increased to 74.5 °C within 3s by low-power NIR laser irradiation, and after 30s of uninterrupted irradiation, it reaches a stable temperature of 118 °C. Therefore, this work introduces new potential for the development of photothermal and wave-absorbing composite materials.

[0090] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A near-infrared laser photothermal conversion and wave absorbing composite material, characterized in that: The composite material uses a cotton-derived carbon film as a substrate, and CoFe layered double hydroxide and a Co metal organic framework are sequentially loaded on the substrate.

2. A method for preparing the near-infrared laser photothermal conversion and wave absorbing composite material as claimed in claim 1, characterized in that: The following steps are involved: Dissolving cobalt nitrate and iron nitrate in pure water, adding urea and ammonium fluoride and stirring to obtain a precursor solution; immersing the cleaned cotton fabric in the precursor solution for hydrothermal reaction; Cobalt nitrate and 2-methylimidazole are dissolved in water respectively and then mixed to obtain a mixed solution. The sample after the hydrothermal reaction is immersed in the mixed solution for aging, washing, drying, pyrolysis and carbonization treatment to obtain a near-infrared laser photothermal conversion and wave absorbing composite material.

3. The method for preparing the near-infrared laser photothermal conversion and wave absorbing composite material according to claim 2, characterized in that: In the precursor solution, the molar ratio of cobalt in cobalt nitrate to iron in ferric nitrate is 1:1; and / or the molar ratio of urea to ammonium fluoride is 1:

1.

4. The method for preparing the near-infrared laser photothermal conversion and wave absorbing composite material according to claim 2, characterized in that: The conditions of the hydrothermal reaction are: heating at 120° C. for 12-18 h.

5. The method for preparing the near-infrared laser photothermal conversion and wave absorbing composite material according to claim 2, characterized in that: In the mixed solution, the molar ratio of 2-methylimidazole to cobalt nitrate is (12.5-13):

1.

6. The method for preparing the near-infrared laser photothermal conversion and wave absorbing composite material according to claim 2, characterized in that: The specific process of the pyrolysis carbonization treatment is: heating to 700-1000° C. at a rate of 5° C. / min under the protection of inert argon in a vacuum tube furnace, and continuously calcining at the corresponding temperature for 1-1.5 hours.

7. An application of the near-infrared laser photothermal conversion and wave absorbing composite material as claimed in claim 1 in the field of military laser shooting and sensing.

8. A near-infrared laser photothermal conversion and wave absorbing flexible composite material, characterized in that: The near-infrared laser photothermal conversion and wave absorbing composite material according to claim 1 is encapsulated in a carbon film by using polydimethylsiloxane to obtain a near-infrared laser photothermal conversion and wave absorbing flexible composite material.

Citation Information

Patent Citations

  • FeCo / Fe2O3 / C fiber composite wave-absorbing material as well as preparation method and application thereof

    CN117126644A